Impression creep test of a P91 steel: a round robin programme. (2nd November 2018) - Brett, S. J.; Dyson, C. N. C.; Purdy, D.; Shingledecker, J.; Rantala, J.; Eaton-Mckay, J.; Sun, W.
Abstract: The process of standardisation of small specimen creep testing techniques, specifically the impression creep test requires the repeatability of the test method. In this study it is accomplished through a round robin programme involving four different labs which have slightly different test set-ups adhering to predefined recommendations stated in previous work. The labs all conducted the same stepped stress test on a reference heat of grade 91 power plant steel and the displacement traces of the tests are analysed to outline the effects of different test set-ups and their efficacies. Main differences are in temperature control and loading application and control.